TGF-gb (Bin Human Diseases - Moustakas, Aristidis; Miyazawa, Keiji; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
Transforming growth factor-gb (B(TGF-gb(B) is a secreted polypeptide with multifunctional properties manifested during embryonic development, adult organ physiology, and pathobiology of major diseases, including cancer and fibrotic and cardiovascular diseases. The signaling pathway of TGF-gb (Bnow is rather well understood. Continuing revelations in the mechanisms of action of TGF-gb (Bprovide specific mechanistic examples of how human cells lose their controlled function and behave wrongly during the development of diverse diseases. Equally important, however, is the current promise of exploiting the TGF-gb (Bpathway in combating human disease. This book comprehensively covers major areas of human disease where the involvement of TGF-gb (Bis firmly established. Simultaneously, the book highlights major gaps in knowledge and the future directions of research that can benefit human medical science. The core set of diseases where TGF-gb (Baction is well documented and are included in the book are cancer and cardiovascular and fibrotic disorders. The central aim of the book is to stimulate young scientists to enter the prolific TGF-gb (Bfield and find new solutions to the problems remaining in this area of study. For this purpose the book provides authoritative educational chapters that furnish a good introduction to the field for young doctoral students, postdocs, and clinical fellows. The book also serves as a valuable reference for the aficionados in the field, who can find accessible and well-illustrated material for their teaching and lecturing activities, via which the importance of TGF-gb (Bbiology is disseminated to the world of science and to the public.s
Part I Introduction -- 1 Transforming Growth Factor-gb (BSignaling -- 2 TGF-gb (BSignaling in Stem Cell Fate Determination -- 3 Emerging Roles of TGF-gb (BCo-receptors in Human Disease -- Part II Cancer, Fibrosis, and Inflammation -- 4 TGF-gb (Bin Cancer Stem Cells -- 5 TGF-gb (Bas Tumor Suppressor: In Vitro Mechanistic Aspects of Growth Inhibition -- 6 TGF-gb (Bas Tumor Suppressor: Lessons from Mouse Models -- 7 The Multifunctional Roles of TGF-gb (Bin Navigating the Metastatic Cascade -- 8 TGF-gb (BSignaling in Leukemogenesis -- 9 TGF-gb (Bin Skin Cancer and Fibrosis -- 10 The Role of TGF-gb (Bin Cutaneous Melanoma Biology -- 11 The Transforming Growth Factor-Beta (TGF-gb(B) in Liver Fibrosis -- 12 TGF-gb (Band Inhibitory Smads in Inflammation -- Part III Cardiovascular Diseases -- 13 TGF-gb (Band Cardiovascular Disorders -- 14 TGF-gb (BSignaling in Physiological and Pathological Angiogenesis -- 15 TGF-gb (BSignaling Pathway and MicroRNAs in Cardiovascular Disease -- Part IV Other Diseases -- 16 TGF-gb (Band Genetic Skeletal Diseases -- 17 TGF-gb (Bin Brain Disorders -- 18 TGF-gb (Band Metabolic Homeostasis -- Part V Disease Prognosis and Therapy. 19 Targeting Pro-Angiogenic TGF-gb (BSignaling in the Tumor Microenvironment.s
Keywords: Life sciences; Oncology; Cytokines; Cytology; Life Sciences; Cytokines and Growth Factors; Cell Biology; Cancer Research